Thermochromic and solvatochromic properties of Lindqvist polyoxometalates - Herrmann, Sven; Margraf, Johannes; Clark, Timothy; Streb, Carsten (Chemical Communications, 2015)
The thermochromic and solvatochromic properties of Lindqvist metal oxide clusters [VxM6-xO19](n-) (x = 0, 1, 2, M = Mo, W) are reported. The cluster anions show pronounced changes of their electronic structure depending on their chemical environment (e.g. solvent polarity, temperature). These are rationalized using experimental and theoretical methods. A combined density functional theory and V-51-NMR study suggests that temperature-dependent changes in the structural dynamics of the metal oxide framework are the underlying cause for the observed thermochromism. The results might open new avenues for the design of molecular optical sensors.